4-Cyclobutylamino-3-nitrobenzoic acid - Narendra Babu, Shivanagere Nagojappa (International Union of Crystallography, 2009)
The asymmetric unit of the title compound, C(11)H(12)N(2)O(4), contains two crystallographically independent molecules with similar geometries. Both molecules contain an intramolecular N—H⋯O hydrogen bond. The dihedral angles between the benzene ring and the mean plane of the cyclobutane ring are 38.29 (7) and 57.04 (8)° in the two molecules, and the nitro group is twisted slightly away from the plane of the benzene ring [dihedral angles = 9.15 (12) and 9.55 (12)° in the two molecules]. In the crystal, the independent molecules are linked into dimers by O—H⋯O hydrogen bonds between their carboxyl groups, and C—H⋯O and C—H⋯π interactions are formed between dimers.